2021
DOI: 10.3390/ani11010184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stocking Density and Carbon Sources on the Oxidative Status, and Nonspecific Immunity of Nile tilapia (Oreochromis niloticus) Reared under Biofloc Conditions

Abstract: The present study investigated the effect of stocking density and dietary carbon sources on the water quality, oxidative status, and immune-related genes of Nile tilapia (Oreochromis niloticus) reared under biofloc conditions (BFT). Eight groups were established at two levels of stocking densities (140 fish per m3: low stocking density, LSD) and (280 fish per m3: high stocking density, HSD) (5.15 ± 1.12 g) and kept in eight biofloc units containing water without carbon sources (control groups) or with glycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 63 publications
(69 reference statements)
1
15
1
Order By: Relevance
“…In the experiment, it was demonstrated that the biofloc system significantly enhances shrimp survival, final body weights, and prophenoloxidase (proPO) cascade, which is one of the major innate immune responses in crustaceans, by upregulating prophenoloxidase activation enzyme, masquerade-like proteinase, prophenoloxidase1, prophenoloxidase2, serine proteinase1, and ras-related nuclear protein expression ( Kim et al, 2014 ). Similar findings were also observed in Labeo rohita ( Ahmad et al, 2016 ; Kamilya et al, 2017 ), Oreochromis niloticus ( Mansour and Esteban, 2017 ; Mirzakhani et al, 2019 ; Hwihy et al, 2021 ; Shourbela et al, 2021 ), Cyprinus carpio ( Bakhshi et al, 2018 ; Aalimahmoudi and Mohammadiazarm, 2019 ), and Apostichopus japonicus ( Chen et al, 2018 ), where animals reared in biofloc water display higher growth performance including improved feed efficiency ratio (FER), specific growth rate (SGR), and feed conversion ratio (FCR). Additionally, the cultured animals have enhanced non-specific immune response, highlighted by significantly increased serum protein, serum albumin, total immunoglobulin, lysozyme, respiratory burst, and myeloperoxidase activity.…”
Section: Potential Role Of Biofloc System-induced Microbial Communitysupporting
confidence: 72%
“…In the experiment, it was demonstrated that the biofloc system significantly enhances shrimp survival, final body weights, and prophenoloxidase (proPO) cascade, which is one of the major innate immune responses in crustaceans, by upregulating prophenoloxidase activation enzyme, masquerade-like proteinase, prophenoloxidase1, prophenoloxidase2, serine proteinase1, and ras-related nuclear protein expression ( Kim et al, 2014 ). Similar findings were also observed in Labeo rohita ( Ahmad et al, 2016 ; Kamilya et al, 2017 ), Oreochromis niloticus ( Mansour and Esteban, 2017 ; Mirzakhani et al, 2019 ; Hwihy et al, 2021 ; Shourbela et al, 2021 ), Cyprinus carpio ( Bakhshi et al, 2018 ; Aalimahmoudi and Mohammadiazarm, 2019 ), and Apostichopus japonicus ( Chen et al, 2018 ), where animals reared in biofloc water display higher growth performance including improved feed efficiency ratio (FER), specific growth rate (SGR), and feed conversion ratio (FCR). Additionally, the cultured animals have enhanced non-specific immune response, highlighted by significantly increased serum protein, serum albumin, total immunoglobulin, lysozyme, respiratory burst, and myeloperoxidase activity.…”
Section: Potential Role Of Biofloc System-induced Microbial Communitysupporting
confidence: 72%
“…Using of these chemical substances cause mass killing of beneficial aquatic bacteria [13], produce multi-drugs resistant pathogens [14], and leaving residues in fish which can be transmitted to human [15,16]. These problems are the most concerning aquaculture sustainability [17,18], and infectious diseases and parasitic infestation treatment with natural substances/compounds are the demanding sustainable aquaculture features [19].…”
Section: Introductionmentioning
confidence: 99%
“…These sources include corn flour (García‐Ríos et al, 2019), wheat flour (García‐Ríos et al, 2019), oligosaccharides (Kishawy et al, 2020), sugar (García‐Ríos et al, 2019; Hisano, Barbosa, et al, 2021; Liu, Luo, et al, 2018; Long et al, 2015) and molasses (Hisano, Barbosa, et al, 2021; Khanjani, Alizadeh, & Sharifinia, 2021; Laice et al, 2021). The effectiveness of carbon supplementation depends on the carbon source, quality and quantity, time and frequency of application, total ammonia–nitrogen (TAN) concentration in the water, exogenous supplemental feeds and fish size and stocking density (El‐Sayed et al, 2021; Khanjani, Alizadeh, & Sharifinia, 2021; Shourbela et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…. The analysis of gene expression was performed by comparative threshold cycle method 2 −ΔΔC t(Shourbela et al, 2021).…”
mentioning
confidence: 99%